NETTING SUCCESS: A HOLISTIC EVALUATION OF GILLNET-BASED MARINE CAPTURE FISHERIES IN BAAI ISLAND PORT, BENGKULU - Yohana Romdhon; Mustopa Sukiyono (American Journal Of Agriculture And Horticulture Innovations, 2024)
This study presents a comprehensive evaluation of the performance of gillnet-based marine capture fisheries in the Baai Island Port of Bengkulu. Utilizing both financial and operational metrics, the analysis offers insights into the effectiveness and sustainability of this fishing method in the region. Through rigorous assessment, key factors influencing the success of gillnet fisheries are identified, providing valuable implications for fisheries management and policy formulation.